Catalytic gasification of coal in a decoupled dual loop gasification system over alkali-feldspar. (October 2021) - Khan, Muhammad Mahmood; Xu, Shaoping; Wang, Chao
Abstract: The catalytic gasification of Yuyang coal for the production of hydrogen-rich syngas has been performed in a novel decoupled dual loop gasification system using alkali-feldspar as an in-situ catalytic bed material. This experimental setup is comprised of a fluidized bed gasifier (FBG), a moving bed reformer (MBR), a riser combustor (RC) and a particle grading cyclone (PGC). By the PGC, two loops, i.e. a gasification loop with quartz sand as circulating bed material between the FBG and the RC and a reforming loop with alkali-feldspar as circulating bed material between the MBR and the RC, are formed. The effects of process parameters such as reformer temperature (700–850 °C), steam/coal ratio (S/C) (0.6–1.5) and air equivalence ratio (ER) (0.15–0.30) on the composition of product gas, lower heating value (LHV), tar content, yield of product gas, the carbon and water conversions and the cold gas efficiency were investigated. At the reformer temperature of 850 °C, the lowest tar content 5.8 g/Nm 3 and the maximum yield of product gas 1.0 Nm 3 /kg daf were obtained. The addition of steam increased the H2 yield. The maximum hydrogen concentration of 65.1 vol% in product gas was attained at the S/C ratio of 1.5. Oxygen as a part of gasification agent led to the rise of CO2 concentration from 24.3 to 46.3 vol% and the reduction of H2 concentration from 54.4 to 33.0 vol% with the increase of ER from 0.15 to 0.30. Graphical abstract: Image 1 Highlights: Alkali-feldspar used as a catalytic bed material in the decoupled dual loop gasifier. Alkali-feldspar showed efficient tar removal and product gas quality enhancement. Decoupling and optimization of coal gasification and tar reforming achieved.